2008
DOI: 10.1002/elan.200804233
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Study on DNA Damage Based on the Direct Oxidation of 8‐Hydroxydeoxyguanosine at an Electrochemically Modified Glassy Carbon Electrode

Abstract: The study of DNA damage induced by Fenton reaction (Fe 2þ /H 2 O 2 ) in vitro was performed based on the direct electrochemical oxidation of 8-hydroxydeoxyguanosine (8-OH-dG), the biomarker of DNA oxidative damage, at an electrochemically modified glassy carbon electrode (GCE). The effects of antioxidants, such as ascorbic acid, and hydroxyl-radical scavenger (mannitol) on the DNA damage were also investigated. 8-OH-dG, the oxidation product of guanine residues in DNA, has shown significantly oxidative peak on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…For dGMP and dCMP, good conversion rates were achieved, allowing advanced structure elucidation of dGMP oxidation products by ESI-MS/MS. Further developments in the electrochemical technique, for example the combination of the direct electrochemical oxidation with Fenton reactions [14], have the potential to further increase the oxidative conversion of nucleotides. The comparison of the presents results with oxidative DNA damage occurring in the organism shows that the formation of mutagenic DNA lesions like 8-oxo-dGMP, 2'-deoxy-5-hydroxycytidine 5'-monophosphate, 2'-deoxycytidine glycol 5'-monophosphate as well as hydroxylated dUMP and dTMP species was successfully achieved in the EC-MS setup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For dGMP and dCMP, good conversion rates were achieved, allowing advanced structure elucidation of dGMP oxidation products by ESI-MS/MS. Further developments in the electrochemical technique, for example the combination of the direct electrochemical oxidation with Fenton reactions [14], have the potential to further increase the oxidative conversion of nucleotides. The comparison of the presents results with oxidative DNA damage occurring in the organism shows that the formation of mutagenic DNA lesions like 8-oxo-dGMP, 2'-deoxy-5-hydroxycytidine 5'-monophosphate, 2'-deoxycytidine glycol 5'-monophosphate as well as hydroxylated dUMP and dTMP species was successfully achieved in the EC-MS setup.…”
Section: Discussionmentioning
confidence: 99%
“…Besides bare electrode surfaces, modified glassy carbon electrodes have been implemented for studying DNA oxidation processes. [13,14]. Electrochemical DNA sensors, generally consisting of single stranded DNA, immobilized on glassy carbon electrode surfaces, can bind highly specific to target DNA strands [15].…”
Section: Introductionmentioning
confidence: 99%
“…The RSD was 3.2% at 1 µmol l −1 . Zhang et al (2008) reported the study of DNA damage induced by Fenton system on a glassy carbon electrode (GCE) and its pro-tection with the antioxidant ascorbic acid. These authors verified that ascorbic acid promoted protective effect on the DNA in a nar-row concentration range (from 1.5 to 2.5 mmol l −1 ) while at lower concentrations, a prooxidant role was observed.…”
Section: Determination Of Antioxidant Capacitymentioning
confidence: 99%
“…Zhang et al (2008) reported the study of DNA damage induced by Fenton system on a GCE and its protection with the antioxidant ascorbic acid. Ascorbic acid promoted protective effect on the DNA in a narrow concentration range (from 1.5 to 2.5 mmol l -1 ) (Zhang et al, 2008). Nobushi and Uchikura (2010) reported the protective effects on the DNA by applying ascorbic acid as a scavenging antioxidant.…”
Section: +mentioning
confidence: 99%